Atrial lead perforation early after device implantation—a case report and literature review - Wang, Zefeng; Yuan, Zhongyu; Li, Haiwei; Zhang, Ke; Zhang, Hongkai; Li, Xiaoyan; Wang, Changhua; Tian, Yilun; Shen, Yiqing; Zhang, Xiaoping; Wu, Yongquan (Frontiers in Surgery, 2024)
We report three patients with screw-in lead perforation in right atrial free wall not long after device implantation. All the patients complained of intermittent stabbing chest pain associated with deep breathing during the implantation. The "dry" epicardial puncture was utilized to avoid hemopericardium during lead extraction in the first case. The atrial electrode was repositioned in all cases and replaced by a new passive fix lead in 2 patients with resolution of the pneumothorax or pericardial effusion. A literature review of 50 reported cases of atrial lead perforation was added to the findings in our case report.